A criteria of completeness for compact operators in Hilbert space - Alcántara Bode, Julio (Pro Mathematica, 2004)
A necessary and sufficient condition is given for completeness of the set of eigenfunctions and generalized eigenfunctions associated to the non zero eigenvalues of a compact operator on a Hilbert Space.